2015
DOI: 10.1002/ange.201501394
|View full text |Cite
|
Sign up to set email alerts
|

LP99: Discovery and Synthesis of the First Selective BRD7/9 Bromodomain Inhibitor

Abstract: The bromodomain‐containing proteins BRD9 and BRD7 are part of the human SWI/SNF chromatin‐remodeling complexes BAF and PBAF. To date, no selective inhibitor for BRD7/9 has been reported despite its potential value as a biological tool or as a lead for future therapeutics. The quinolone‐fused lactam LP99 is now reported as the first potent and selective inhibitor of the BRD7 and BRD9 bromodomains. Development of LP99 from a fragment hit was expedited through balancing structure‐based inhibitor design and biophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 24 publications
0
69
0
Order By: Relevance
“…The SGC and the University of Oxford published LP99 (Fig. 4), a potent and selective inhibitor for both BRD9 and BRD7 bromodomains, which plays a role in regulating pro-inflammatory cytokine secretion 127 . Two other BRD9 inhibitors, BI-7273 and BI-9564, were described by Boehringer Ingelheim and the SGC (Fig.…”
Section: Bromodomain Inhibitorsmentioning
confidence: 99%
“…The SGC and the University of Oxford published LP99 (Fig. 4), a potent and selective inhibitor for both BRD9 and BRD7 bromodomains, which plays a role in regulating pro-inflammatory cytokine secretion 127 . Two other BRD9 inhibitors, BI-7273 and BI-9564, were described by Boehringer Ingelheim and the SGC (Fig.…”
Section: Bromodomain Inhibitorsmentioning
confidence: 99%
“…[12,14,15] To explore the potential of bifunctional derivatives to induce BRD9 degradation, we initially selected as our starting point a close chemical analog of I-BRD9 described by GlaxoSmithKline (GSK-39). [14] This ligand was attractive in that it offered high binding affinity (IC50 = 7.9 nM) as well as a solvent exposed methoxy substituent amenable to chemical derivatization.…”
Section: Hhs Public Accessmentioning
confidence: 99%
“…Several BRD9-dircted efforts in discovery chemistry have been reported, [11][12][13][14][15] developing chemotypes for BRD9-specific engagement. A recent study further suggested BRD9 as a dependency in acute myeloid leukemia (AML), where bromodomain inhibition prompted a cytostatic response.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, research by the University of Oxford and the SGC, led to the discovery of LP99 (8) as the first reported dual BRD7/9 chemical probe(Figure 2a)[36]. Using fragment quinolone 7 as a start point, LP99 (8) was developed using structure-based design to guide introduction of a 4-methyl group to occupy a shallow hydrophobic pocket and a complex lactam to the quinolone 7-position to obtain the desired potency and selectivity(Figure 3b).…”
mentioning
confidence: 96%